2014
DOI: 10.1002/jbmr.2294
|View full text |Cite
|
Sign up to set email alerts
|

Human Osteoclasts Are Inducible Immunosuppressive Cells in Response to T cell–Derived IFN-γ and CD40 Ligand In Vitro

Abstract: Osteoclasts (OCs) are bone resorbing cells whose activity can be regulated by activated T cells and their cytokines. However, the immune function of OCs is largely unknown. In this study, we found that as bystanders, human OCs effectively suppressed T-cell proliferation induced by allogeneic, microbial antigenic and T-cell receptor stimuli in vitro. Mechanistic studies revealed that T cell-derived IFN-γ and CD40 ligand (CD40L) induced the expression of indoleamine 2,3-dioxygenase (IDO) in OCs, which mediated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…T cells require adequate Trp levels for survival and effector function; therefore, IDO-mediated Trp deficiency results in T-cell tolerance and impaired effector function, as well as promotes the differentiation of naive CD4 T cells into regulatory T cells. 40 Consistent with a precious study, 41 we also show that IDO in OCs mediates the immunosuppression of T cells. IDO was significantly increased in BM plasma of MM patients.…”
Section: Discussionsupporting
confidence: 90%
“…T cells require adequate Trp levels for survival and effector function; therefore, IDO-mediated Trp deficiency results in T-cell tolerance and impaired effector function, as well as promotes the differentiation of naive CD4 T cells into regulatory T cells. 40 Consistent with a precious study, 41 we also show that IDO in OCs mediates the immunosuppression of T cells. IDO was significantly increased in BM plasma of MM patients.…”
Section: Discussionsupporting
confidence: 90%
“…Menopausal estrogen decline leads to proliferation and activation of T cells by increasing MHCII expression on monocytes and APC function and by inhibiting T cell apoptosis. These effects leads to the expansion of activated T lymphocytes resulting in hyperproduction of inflammatory cytokines and chronic OC stimulation which is responsible for bone loss and increased fracture risk [76,77]. …”
Section: Menopausal and Senile Osteoporosismentioning
confidence: 99%
“…1 More recently it has been suggested that IFNg is responsible for the ability of OCs to act as antigen presenting cells (APCs) and to modulate T-cell proliferation. 4 TNFa and RANKL are well known pro-osteoclastogenic cytokines. 5 TNF-a induces OC formation in the presence of adequate levels of RANKL, 5 upregulates stromal cell production of RANKL and increases the responsiveness of OC precursors to RANKL.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%